2021
DOI: 10.24018/ejbmr.2021.6.6.1113
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Usability Scale System as an Evaluation of the Kampung Heritage Kajoetangan Guide Ebook Application

Abstract: The development of information technology these days allows tourists to get information about tourist destinations very easily. One of the ways to get information about tourist destinations is from a guidebook. The purpose of this study is to evaluate the Kampung Heritage Kajoetangan's e-book application using the System Usability Scale method. The data was collected using a questionnaire. The respondents of this study are 40 people. The results show that the respondents considered the Kajoetangan travel guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Following our comprehensive usability testing, we have determined that the total value accrued was 10,180, which we then divided by 140, resulting in a score of 72.19. These findings indicate that the virtual tour system can be categorized as "good" [44], [45]. Including images in a 360-degree view can provide a more comprehensive understanding of a location and lead to more accurate information than non-panoramic images [5].…”
Section: Resultsmentioning
confidence: 86%
“…Following our comprehensive usability testing, we have determined that the total value accrued was 10,180, which we then divided by 140, resulting in a score of 72.19. These findings indicate that the virtual tour system can be categorized as "good" [44], [45]. Including images in a 360-degree view can provide a more comprehensive understanding of a location and lead to more accurate information than non-panoramic images [5].…”
Section: Resultsmentioning
confidence: 86%
“…For our usability study, we chose to use the System Usability Questionnaire (SUS), as shown in Table 4 [76], [77]. The SUS is a widely accepted standard tool for assessing Mobile Recommendation System to Provide Emotional Support and Promote Active Aging for Older Adults in the Republic of Panama how users perceive the usability of a system.…”
Section: Measuring Instrumentmentioning
confidence: 99%
“…This test aimed to measure users' satisfaction with the systems' use. Usability testing could assist designers in determining if the designed system or product is in line with users' demands or not [27]. SUS is a comprehensive evaluation of usability factors (effectiveness, efficiency, and satisfaction) as users subjectively feel them.…”
Section: Sus Score For Safeformmentioning
confidence: 99%